Philosophical Reflections on New Foundations of Mental Health: The Personality Modulation Clinic - Alireza Farnam (University of Tabriz, 2021)
To date, of essential goals in psychiatry and establishment of future medical centers is creating therapeutic environments with the aim of improving clinical outcomes, preventing the progression of personality difficulties to serious psychiatric disorders, increasing self-satisfaction in society, facilitating personal growth and actualization, as well as reducing high medical costs. In this regard, the Personality Modulation Clinic in 2016 in Tabriz University of Medical Sciences was established, with the aim of providing appropriate mental health services for clients who do not fulfill criteria for a specific mental disorder, in the traditional classifications; nevertheless, desiring to eliminate inner obstacles towards mental growth, self-actualization, spirituality and the proper well-being they lack. The services in this clinic provide clients with support in order to seek innovative growth opportunities within themselves, by removing inner obstacles towards personality development. These obstacles are roughly equivalent to the diagnosis of “personality difficulty” in the 11th edition of the International Classification of Diseases (ICD-11). Moreover, the therapeutic foundation of this clinic is an emerging medical paradigm known as Cosmetic Psychiatry. At the beginning of any new scientific establishment, as usually happens, and was true for this clinic as well, the bond of philosophical concepts are unveiled, and this is the irreversible and undeniable link between science and philosophy. Thereby, important questions appeared, which were approached philosophically.